A multi‐disciplinary approach to chronic cough in children. Issue 2 (23rd March 2022) - Mukerji, Shraddha S.; Yenduri, Naga Jaya Smitha; Chiou, Eric; Moonnumakal, Siby P.; Bedwell, Joshua R.
Abstract: Objectives: (1) To highlight the important causes of chronic and recurrent cough in children. (2) To discuss multidisciplinary approach to management of chronic/recurrent pediatric cough. Methods: Review of scholarly articles, guidelines, expert panels via PubMed and Google Scholar. Conclusion: Chronic cough (CC) in children is mainly attributed to persistent bacterial bronchitis, asthma, nonspecific cough, and gastroesophageal reflux disease (GERD) symptoms. A multi‐disciplinary approach is cost‐effective and aids with earlier diagnosis and appropriate treatment. Congenital or acquired narrowing of the subglottis is the leading ENT cause for recurrent croup (RC) in children. Laryngeal cleft‐type 1 is commonly seen in children with recurrent aspiration and CC. Children are usually referred to pulmonologists for wet cough not responding to treatment. Eosinophilic esophagitis (EoE) and GERD should be considered in the differential diagnosis of CC in children with both respiratory symptoms and failure to thrive. Level of Evidence: 2a